Parallel algorithms on some numerical techniques using PVM platform on a cluster of workstations - Alias, Norma (Advanced Technology Council in mathematics, Inc, 2002)
In this paper, a few parallel algorithms are explained in solving one dimensional heat model problem using Parallel Virtual Machine (PVM). This research focuses on two iteration methods, Iterative Alternating Decomposition Explicit Method (IADE) and Alternating Group Explicit Scheme (AGE). Conjugate Gradient (CG) is selected as an alternative method to accelerate the convergent and efficiency of these two iteration methods.